2020
DOI: 10.1080/2162402x.2020.1806662
|View full text |Cite
|
Sign up to set email alerts
|

IDH-mutant gliomas harbor fewer regulatory T cells in humans and mice

Abstract: The metabolic gene isocitrate dehydrogenase 1 (IDH1) is commonly mutated in lower grade glioma (LGG) and secondary glioblastoma (GBM). Regulatory T cells (Tregs) play a significant role in the suppression of antitumor immunity in human glioma. Given the importance of Tregs in the overall framework of designing immune-based therapies, a better understanding on their association with IDH mutational status remains of critical clinical importance. Using multispectral imaging analysis, we compared the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Recently, IDH mutation status has been reported to be associated with PD-L1 expression and tumor-infiltrating lymphocyte (TIL) infiltration in diffuse gliomas. 23 , 24 , 25 , 26 , 27 Our study was largely in agreement with available data but differed in several important aspects. We integrated IDH mutation and 1p/19q codeletion status and conducted a comprehensive and systematic analysis of 28 immune cell types and their infiltration in these subtypes; the expression of the immune checkpoint components in each subtype was assessed and TMB, MSI, and MHC class I gene expression was categorized in these subtypes.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, IDH mutation status has been reported to be associated with PD-L1 expression and tumor-infiltrating lymphocyte (TIL) infiltration in diffuse gliomas. 23 , 24 , 25 , 26 , 27 Our study was largely in agreement with available data but differed in several important aspects. We integrated IDH mutation and 1p/19q codeletion status and conducted a comprehensive and systematic analysis of 28 immune cell types and their infiltration in these subtypes; the expression of the immune checkpoint components in each subtype was assessed and TMB, MSI, and MHC class I gene expression was categorized in these subtypes.…”
Section: Discussionsupporting
confidence: 86%
“…15,16 In addition to effector T-cell subsets, our group recently showed a significant reduction in suppressive regulatory T cells (Tregs) in IDH-mutant tumors. 17 In an investigation of a large cohort of diffuse glioma, Berghoff and colleagues showed that the expression of PD-L1, an immunosuppressive cell surface molecule that downregulates T-cell activity, was significantly reduced in IDH-mutant tumors. 16 Recent work by Friebel et al and Mathewson et al further interrogated the transcriptional profiles of tumor-infiltrating T cells and compared their activation states between IDH mutational status.…”
Section: The Immune Landscape Of Mutant Idh: a Brief Overviewmentioning
confidence: 99%
“…15,22 This diminished immune phenotype exhibited by IDH-mutant tumors has been consistently recapitulated in human samples and by other groups studying the immunological consequence of mutant IDH. 16,17,19,20,25 The distinctive immune milieu in IDH-mutant tumors (Fig. 1) may be relevant when developing immune modulating strategies in the future for this molecular class of patients.…”
Section: The Immune Landscape Of Mutant Idh: a Brief Overviewmentioning
confidence: 99%
“…Treg cannot be detected in normal brain, and they are rare in low-grade brain tumors, yet despite lymphopenia, Treg frequencies are increased in the TME as well as in the blood of GBM patients (212)(213)(214)(215). Frequencies may vary by GBM subtype, with the IDH wildtype (Iso-citrate dehydrogenase) and mesenchymal subtypes having higher Treg frequencies than IDH mutated (216) and proneural and classical GBM subtypes, respectively (217). It has been reported that there is an age-dependent increase in the Treg : CD8 + ratio, with a maximal increase in the 60-69 years age group, which coincides with the median age (64 years) of GBM patients at diagnosis (218).…”
Section: Regulatory T Cellsmentioning
confidence: 99%